Performa Reproduksi dan Mortalitas Kambing Lokal di Lahan Perkebunan Rakyat Desa Kayu Lompa - Kusrianty, Nelly; Rinaldy, I Kadek Yudi (MACROCEPHALON : Jurnal Ilmu Peternakan, 2025)
Goats have good adaptability to tropical environments; however, scientific information regarding the reproductive performance and mortality rate of local goats under smallholder farming systems remains limited. This study aimed to evaluate the reproductive characteristics and mortality of local goats raised in smallholder plantation systems. The research employed a quantitative descriptive method with a survey approach. Data were collected through field observations, structured interviews with farmers, and recording of biological parameters of the animals. Data analysis was carried out descriptively by calculating means, standard deviations, and percentages, which were then compared with relevant literature. The results showed that local goats in Kayu Lompa Village had an average age at first estrus of 6.45 months, age at first mating of 7.18 months, and age at first kidding of 13.18 months. The average gestation length was 5.64 months with a kidding interval of 6.73 months. The average litter size was 2.00 kids per kidding with a birth weight of 1.045 kg, while the average weaning age was 4 months. The sex ratio of kids born was 1:2 (male:female). The mortality rate of kids was 2.44% and adult does 3.40%, which are considered low compared to previous reports. This study provides empirical data on the reproductive performance and mortality of local goats under smallholder plantation systems, which can serve as a basis for improving herd management, enhancing productivity, and supporting the development of local goat genetic resources in Indonesia.